2005
DOI: 10.1002/cncr.21492
|View full text |Cite
|
Sign up to set email alerts
|

Estimating late adverse events using competing risks after autologous stem‐cell transplantation in aggressive non‐Hodgkin lymphoma patients

Abstract: BACKGROUND Consolidative autologous stem‐cell transplantation (ASCT) is a valuable option in high‐risk or disease recurrence large‐cell non‐Hodgkin lymphoma patients (NHL); however, its long‐term toxicity must still be assessed. METHODS Among the 439 lymphoma patients transplanted at our institution from January 1, 1993, to January 1, 2002, 158 exhibited aggressive NHL. The median age of the patients was 46 years (range, 18–69), 98 males and 60 females. Ninety (57%) patients received first‐line ASCT. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…21,26,27 Transplantation Modalities Peripheral blood stem cell cryopreservation, thawing, and reinfusion procedures were performed according to standard guidelines. 28,29 Patients were treated with HDT and ASCT if they reached partial remission (PR), CR, or CRu after chemotherapy. They received a conditioning chemotherapy regimen with or without radiation therapy.…”
Section: Fdg-pet/ct Imagingmentioning
confidence: 99%
“…21,26,27 Transplantation Modalities Peripheral blood stem cell cryopreservation, thawing, and reinfusion procedures were performed according to standard guidelines. 28,29 Patients were treated with HDT and ASCT if they reached partial remission (PR), CR, or CRu after chemotherapy. They received a conditioning chemotherapy regimen with or without radiation therapy.…”
Section: Fdg-pet/ct Imagingmentioning
confidence: 99%
“…Previously, age and cardiac dysfunction were accepted as more restrictive, but today, the transplantation applied to older patients may lead to an increased incidence of impaired cardiac function (7-9). Ruiz-Soto et al (10) reported the rate of patients developing left ventricular dysfunction as 6% in their study, wherein they evaluated 493 patients with aggressive NHL who underwent AHSCT. Only 2% of these patients were reported as symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz-Soto et al (10) followed 439 aggressive NHL patients who underwent AH-SCT for a median of 3 years after transplantation in terms of late complications. The number of the patients with late complications was 68, and renal failure was identified only in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Study characteristics are presented in Table 2 [27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Cervical Cancermentioning
confidence: 99%